Analysis of Income and Risk of Rice Seed Breeding Business in the Seed Independent Program in Lekopancing, Maros Regency, South Sulawesi, Indonesia - St. Rahbiah; Nurliani; Ida Rosada; Fifi Nur Fadillah; Sitti Nurani Sirajuddin (Migration Letters, 2023)
The seed breeding business is very dependent on nature such as weather, temperature, drought, floods, pest attacks, and disease. Apart from natural factors, risks can be caused by the farmers’ activities. The seed Mandiri Program is a priority program of the South Sulawesi Provincial Government by providing free superior rice seeds. As one of the largest rice-producing provinces in Indonesia, this program was implemented to boost rice production. Rice seeds come from breeding results carried out at seed installations in South Sulawesi involving breeder farmers. The research aims to calculate the production and income of farmers from the rice seed breeding business in the Mandiri Seed Program, analyse the level of risk of the rice seed breeding business, and describe the efforts made to minimize the risks of the rice seed breeding business. Data analysis methods use descriptive analysis, income analysis, and business risk analysis. The research results show that: 1) the production of rice seeds from the Mandiri Seeds Program is 4,647.5 kg/farmer or 6,885.19 kg/per hectare and an average income of IDR 24,296,222 per farmer or IDR. 35,994,403.4 per hectare 2) the level of production, price, and income risk is included in the low-risk category 3) efforts made by farmers to minimize production, price, and income risks, namely protecting plants from pest and disease attacks, holding back sales until prices are stable, and reduce production costs.